TOXICITY OF HEAVY METALS TO INDIAN MAJOR CARP, LABEO ROHITA (HAM.) - SINGH, ARUN KUMAR; RANA, K.S.; SOLANKI, SUNITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The toxic effect of Cadmium chloride (CdCl3) and Lead nitrate Pb(Nos.), has been recorded on Indian major carp, Labeo rohita (Ham) in order to determine the survival range. LCso values and safe concentration, Cadmium was found to be more toxic than Lead as inferred by their LCso values. The safe concentration of Cadmium chloride and Lead nitrate, as the general representative compounds, were estimated at 5.89 and 6.81 mg/l, respectively.